The use of antidepressants for physical and psychological symptoms in cancer - Zaini, Syahrir N.; Guan, Ng Chong; Sulaiman, Ahmad Hatim; Zainal, Nor Zuraida; Huri, Hasniza Zaman; Shamsudin, Siti Hadijah (Bentham Science Publishers B.V., 2018)
Cancer patients are commonly associated with various physical and psychological symptoms. In palliative setting, the aims are to relieve those symptoms, improve quality of life, and increase medication adherence among cancer patients. Antidepressants are generally accepted for the treatment of depression among patients with or without cancer. Some other potential benefits of the antidepressants have been reported in cancer patients.